2003
DOI: 10.2302/kjm.52.21
|View full text |Cite
|
Sign up to set email alerts
|

Principle and stability of locking plates

Abstract: A new internal Mini-Locking-System was tested compared with conventional 2.0mm Mini plates. Standardised osteotomies in the angular region of 16 human cadaver mandibles were fixed with a 6-hole-plate at the oblique line. Osteosynthesis and stability of fixation was proofed in a three dimensional in-vitro-model in which functional load was simulated. Comparison of the different osteosynthesis techniques showed that in the case of Miniplate fixation torsion and gapping of the bone fragments occurred following pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
88
0
11

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(104 citation statements)
references
References 4 publications
5
88
0
11
Order By: Relevance
“…Gutwald et al [20] and Pektas et al [21] in a cadaveric study comparing mini-locking system with conventional miniplates, subjected to mechanical loading simulating muscle forces showed the lowest gaps and torsion, best stability at the caudal border in case of mini locking plates. Authors stated that the locking principle prevents stripping, movement and loosening of screws.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Gutwald et al [20] and Pektas et al [21] in a cadaveric study comparing mini-locking system with conventional miniplates, subjected to mechanical loading simulating muscle forces showed the lowest gaps and torsion, best stability at the caudal border in case of mini locking plates. Authors stated that the locking principle prevents stripping, movement and loosening of screws.…”
Section: Discussionmentioning
confidence: 98%
“…They concluded that the possible advantage of locking plate/screw fixation system are theoretical, whether clinical results can be improved could not be measured. Gutwald et al [20] experienced complications in the region of angle followed by parasymphysis and body. Minor infections required hardware removal, and occlusal discrepancy was treated with elastics and enameloplasty.…”
Section: Discussionmentioning
confidence: 99%
“…The biomechanical properties of locking and conventional titanium systems were evaluated by Gutwald et al 7) and Ellis et al 4) . Both were clinical reports and presented positive results, but were conducted on mandibular fracture patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Exact plate adaptation is no longer necessary which should shorten operation times [32][33][34]. The operating time required for the adaptation and fixation of locking plate ranged from 5 to 9 min with a mean time of 6.8 min and the operating time required for the adaptation and fixation of Champy's miniplate ranges from 8 to 14 min with a mean of 10.1 min.…”
Section: Discussionmentioning
confidence: 99%